A Class of Degenerate Nonlinear Elliptic Equations in Weighted Sobolev Space. (25th March 2014) - Kar, Rasmita
Abstract : We prove the existence of a weak solution for the degenerate nonlinear elliptic Dirichlet boundary-value problem L u - μ u g 1 + h u, ∇ u g 2 = f in Ω, u = 0 on ∂ Ω, in a suitable weighted Sobolev space, where Ω ⊂ ℝ n is a bounded domain and h is a continuous bounded nonlinearity.